The effect of trehalose administration on miRNA-10a expression in patients with history of myocardial infarction (MI) and systemic inflammation. (3rd October 2022) - Ganjali, S; Jamialahmadi, T; Banach, M; Sahebkar, A
Abstract: Background: MicroRNAs (miRNAs) are small non-coding RNAs involved in the regulation of endothelial function, inflammatory cells, and cholesterol homeostasis, may cause the onset of vascular inflammation which plays an important role in the development of cardiovascular disease. Trehalose is a nonreducing disaccharide which anti-inflammatory properties have been indicated in different experimental models. Purpose: This study aimed to evaluate the effectiveness of intravenous (IV) trehalose administration on the circulating level of miRNA-10a as a biomarker of coronary inflammation in patients with history of myocardial infarction (MI) and elevated C-reactive protein (CRP). Methods: This was a randomized, double-blind trial comprised 15 men (aged 18–80) with history of MI and evidence of systemic inflammation. The patients were randomly allocated to 2:1 ratio and respectively underwent the injection of either IV trehalose (15 g/week) or placebo for 12 weeks. At baseline and at the end of study, the serum level of miRNA-10a was measured by SYBR Green qPCR, quantified by the comparative method, and normalized to U6 expression. Relative expression software tool (REST) was used to analyze the miRNA-10a fold change (FC) expression level. Results: At the baseline, patients in trehalose group showed slightly lower level of miRNA-10a relative to the placebo group (FC: 0.272, P=0.052), while it was not statistically significant. Within-group analysis showed that miRNA-10a had a significantly lower level in placebo group at the end of the study in comparison with the baseline (FC; 0.19, P=0.029). Albeit, miRNA-10a level increased after trehalose administration in relation to the baseline, while it was not statistically significant (FC: 1.963, P=0.114), Moreover, these changes in miRNA-10a levels were statistically significant in trehalose group related to the placebo group (P=0.047). Conclusions: Together these findings demonstrate that trehalose administration could effectively increase the circulating level of miRNA-10a and may contribute to the regulation of coronary inflammation in patients with a history of MI and elevated CRP levels. This anti-inflammatory effect of trehalose can be confirmed in the large-scale studies or by evaluating other miRNAs related to the vascular inflammatory processes. Funding Acknowledgement: Type of funding sources: None.